Solve the following equation, answer as a reduced, mixed number 4(7 - 3x) = 7(4 - 2x)

Question

Asked 3/7/2013 9:03:18 AM

Updated 7/26/2014 2:08:54 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [7/26/2014 2:08:54 PM]

Narkotiq|Points 337|

ripvic|Points 571|

samn|Points 3844|

Question

Asked 3/7/2013 9:03:18 AM

Updated 7/26/2014 2:08:54 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [7/26/2014 2:08:54 PM]

Rating

3

4(7 - 3x) = 7(4 - 2x);

28 - 12x = 28 - 14x;

-12x + 14x = 28 - 28;

2x = 0;

x = 0

28 - 12x = 28 - 14x;

-12x + 14x = 28 - 28;

2x = 0;

x = 0

Added 7/26/2014 2:08:53 PM

This answer has been confirmed as correct and helpful.

27,089,869

questions answered

There are no comments.